Innovative Biometric Attendance Monitoring System with Analytics for Enhanced Church Management - Bernandino P. Malang; Carmelita O. Tanig (Future Science / FSH-PH Publications, 2026)
The research in this paper aimed at designing, implementing and evaluating the novel biometric attendance monitoring system, integrated with built-in analytics for improving management in a church. Current approaches to attendance monitoring in congregations were often costly, in-accurate, voluminous, and inefficient, resulting in a lack of timely and accurate information for leadership to use in decision making. The suggested solution was to have the R307 fingerprint sensor to be embedded in the centralized MySQL database which would accurately and securely capture the time-in and time-out events with minimal inconvenience to the user. Several church services were conducted, and a 97.5% recognition accuracy for fingerprints and an average time to transact of 1–2 seconds were achieved on average, resulting in significantly less duplicate attendance and proxy check-in records. The system offered real-time dashboards and scheduled analytical reports, enabling administrators to view attendance trends, timeliness, and age group participation. These analytical skills helped to make tactical decisions, such as increasing numbers of ushers during the busiest services and strategic decisions, such as increasing worship time and offering targeted pastoral follow-up activities.The evaluation showed that the overall results of the user acceptance rate based on the Technology Acceptance Model (TAM) were high, with the attitude to use, perceived usefulness and perceived ease of use with excellent ratings of 99.6%, 99.8%, and 99.8%, respectively.